VIABILITY OF THE INTRODUCTION OF A PRODUCING INDUSTRY OF HYDROHONEY - Nakada, Jéssica Pestrini; Caciatori, Lidia Urbano; Pandolfi, Marcos Alberto Cláudio (Revista Interface Tecnológica, 2020)
The present article had since objective boarded the viability of the introduction of an industry of production of hydrohoney, ancient drink produced from the fermentation of the honey, endowed of historical roots. For so much, lifting and subsequent bibliographical revision was carried out, looking for informations about the industry and the product open to question, so that subsequently a business plan was prepared. The strategic analysis was carried out, still, and of market, with the objective of identifying the extern aspects to the enterprise, such as competition, clients and suppliers, as well as, the internal aspects of the producing enterprise of hydrohoney, pointing to the strong points and the intrinsic risks to the product and to the conditions of development, as well as the relevant legislation, the necessary equipments, the costs and receipts, analysing the necessary investments to the development of the proposed plan of business. To the end, study of economical viability was carried out, where it was possible to end what the undertaking shows viable for high production volumes.